Who expert committee on specifications for pharmaceutical preparations; forty sixth report (WHO technical Report Series)
General policy -- Quality control-specifications and tests -- Quality control - international references materials (international chemical substances and infrared reference spectra) -- Quality control - national laboratories -- Quality assurance - good manufacturing practices -- Quality assurance - new approaches -- Quality assurance- distribution and trade of pharmaceuticals -- Prequalification of priority essential medicines including active pharmaceutical ingredients -- Prequalification of quality control laboratories -- Regulatory guidance -- Nomenclature, terminology and databases -- Miscellaneous.